Third-line multiple myeloma treatment of inpatients in a German cancer center: analysis of potential cost savings due to decreased renal insufficiency - F. Jakobs; P. Ahmadi; V. Osterkamp; J. Jeck; U. Holtick; C. Scheid; Florian Kron (Cost Effectiveness and Resource Allocation)
Abstract Background Renal insufficiency is one of the most common complications in the treatment of multiple myeloma (MM). The administration of isatuximab showed improved patient outcome regarding the occurrence of renal insufficiency. Building on the results of the ICARIA-MM study, the aim of this study was to quantify the potential cost savings due to a prevented progress of renal insufficiency. Methods Real-life accounting data of the University Hospital Cologne (Germany) of inpatients with MM between 2016 and 2020 were analyzed regarding the presence of renal insufficiency. The health-economic impact of a less severe renal insufficiency due to improved renal filtration on German Diagnosis-Related Groups (G-DRG) tariffs was modelled. Results The analysis revealed a total of 74 hospital cases with MM. The vast majority (n = 64; 86.5%) were allocated to the G-DRG code R61, summarizing patients with “lymphoma and non-acute leukemia”. Based on a reduction of stage 3 renal failure to stage 2, the model showed cost saving potential in patients with acute renal failure ranging from € 3,101 to € 4,642 per case. Conclusion The analysis quantifies for the first time the economic saving potential of improved renal function in patients with relapsed/refractory multiple myeloma in the German healthcare system through the administration of isatuximab.